Floseal-induced small bowel obstruction. Issue 9 (28th September 2022) - Ashraf, Hamza; Low, Nicholas; Spiro, Calista; Keong, Benjamin
Abstract: Floseal is a haemostatic agent designed to augment the body's natural clotting cascade response. We describe the first case in over a decade, and the first case with intra-operative images of early post-operative small bowel obstruction (SBO) associated with Floseal use in general surgery. A previously well man in his 30s underwent laparoscopic appendicectomy for clinical acute appendicitis. Floseal was applied to the right lateral abdominal wall for haemostasis. He developed a mechanical SBO, with diagnostic laparoscopy confirming a transition point between the caecum and terminal ileum, adherent to the area of the previously applied Floseal. He underwent adhesiolysis and uneventful recovery. We propose Floseal may exacerbate early post-operative inflammation and provide a nidus for early adhesion formation. We recommend removing excess Floseal not incorporated in the haemostatic clot and to consider Floseal as a differential in early post-operative SBO.